Evaluation of the Implementation of Tax Incentive Policy for Small and Medium Enterprises Affected by the Covid-19 Pandemic at the Tax Service Office Pratama Koja Utara Jakarta - Winda Wulandari; Fransiskus Christanto Kia Teron; Dwi Agustina; Eka Rofiyanti (Yayasan Ilomata, 2022)
The Covid 19 pandemic in almost all countries, including Indonesia, has negatively impacted the economic sector, especially the MSME business. The government has made various efforts to restore the Indonesian economy. Through the Directorate General of Taxes, under the authority of the Ministry of Finance, the government decided to provide tax incentives for taxpayers affected by the Covid 19 pandemic. This final income tax incentive is based on the Regulation of the Minister of Finance of the Republic of Indonesia No. 44 PMK/03/2020. This regulation focuses on Small and Medium Enterprises. Taxes are usually 0.5% of gross income that is self-paid or deducted or collected by withholders or collectors. However, with PMK-44/PMK.03/2020, the tax is borne by the government, which means that the income is not subjected to tax from April 2020 to December 2020. This study used a descriptive method. The data was collected through a literature study where the author evaluated the implementation of government regulatory policies regarding applying tax incentives for MSMEs affected by Covid-19. The purpose of providing tax incentives to MSMEs is to reduce their difficulty in meeting operational costs or expenses so that MSMEs can survive during the pandemic, as well as save the national economy and maintain financial system stability. The study results show that tax incentives and relaxation and the provision of tax incentives to the beneficiary sector MSME are productive and able to support the recovery of the national economy. These programs and tactical steps ensure that economic growth is maintained even though these programs are separate and unrelated to the spread of Covid-19, which can be controlled quickly.